Solid-State Synthesis and Thermoelectric Properties of Ge-Doped Tetrahedrites Cu12Sb4-yGeyS13 - Jeong, Se-In; Kim, Il-Ho (Korean Journal of Metals and Materials, 2022)
Ge-doped tetrahedrites Cu12Sb4-yGeyS13 (y = 0.1–0.4) were prepared using mechanical alloying and hot pressing. An X-ray diffraction analysis after mechanical alloying showed a single tetrahedrite phase without secondary phases. The tetrahedrite phase was stable after hot pressing at 723 K under 70 MPa. As the Ge content increased, the lattice constant decreased from 1.0343 to 1.0334 nm, which confirms that Ge was successfully substituted at the Sb sites. Ge-doped tetrahedrites exhibited p-type semiconductor characteristics. When Ge4+ was substituted for Sb3+, additional electrons were generated. Thus, the electrical conductivity decreased and the Seebeck coefficient increased due to the decrease in carrier (hole) concentration. For the Ge-doped specimen with y = 0.1, a maximum power factor of 0.87 mWm-1K-2 was obtained at 723 K. As the Ge content increased, the power factor decreased. However, as the Ge content increased, the electronic and lattice thermal conductivities decreased. Therefore, the substitutions of Ge at the Sb sites intensified both ionization impurity scattering and phonon scattering, resulting in very low thermal conductivities of 0.4–1.0 Wm-1K-1 at 323–723 K for y = 0.1–0.4. As a result, the highest dimensionless figure of merit ZT = 0.74 was obtained at 723 K for Cu12Sb3.8Ge0.2S13.